FETAL HYDROPERITONEUM AS A CAUSE OF DYSTOCIA IN A BUFFALO - PANDEY, ANAND KUMAR; SINGH, GYAN; PHOGAT, J B (The Indian Journal of Animal Reproduction, 2011)
A rare case ofdystocia due to fetal hydroperitoneum and its successful delivery through vagina is described.
Keywords: Buffalo; Oystocia; Hydroperitoneum